A practice in a research methodology class / Teoh Sian Hoon and Parmjit Singh. - Teoh, Sian Hoon; Singh, Parmjit (2019)
There are challenges in teaching research methodology as highlighted by many researchers. Among the challenges are strategies for putting material in context. For achieving this purpose, students’ engagement in the learning process needs to be re-looked. This paper shares on a practice engaging students in a research methodology class. The practice aims to assist active learning among the students as informed by the constructivist learning theory. Specifically, a teaching philosophy focuses in applying The Zone of Proximal Development (ZPD) is highlighted. An action research was conducted to investigate how the students learn a topic of research methodology within the practice of ZPD. The action research aims to bridge the gap between research and the practice putting material in the context of learning. The findings of this study showed that students found research methodology a difficult subject, but they experienced good discussion and engaged themselves in the classroom discussion. The discussion assists them in recalling and memorising as well as creating more examples for the context of learning. Nevertheless, they need more meaningful materials to support their learning.